Cultural representation in the ELT textbook "Work in Progress" - Alfaya, Anfa Farkhan; Rochsantiningsih, Dewi; Sumardi, Sumardi (Diksi, 2023)
The present study uncovered the cultural contents of the Indonesian ELT textbook for tenth-grade secondary-level students Bahasa Inggris "Work in Progress" based on the cultural types using content analysis. The book is chosen because it is nationally used and based on the curriculum Merdeka 2022. This study focused on analyzing the cultural contents, represented with graphical images integrated with text (e.g., pictures with monologue, dialogue, or description). The findings showed that among the four types of culture, the Target culture was dominantly represented in the textbook 59 times (50,9%). Then, it was followed by the culture neutral 23 times (19,8%), the international culture 18 times (15,5%), and the last source culture 16 times (13,8%). The various and well-organized cultural content proportion should be put more attention.